APPLICATION OF NON FUNGIBLE TOKENS (NFT’s) IN INDIAN BUSINESSES - S, Dr. Umakanth; Kumar S, Dr. Hemanth; S, Dr. Mahalakshmi (The journal of contemporary issues in business and government, 2023)
A thorough evaluation of the financial markets as well as the business sector is essential as block chain technology and Non Fungible Tokens (NFTs) continue to develop in the digital global environment. The goal of this research is to determine whether or whether the market is ready, willing, and able to make use of digital tokens of this type. Overall, this research is aimed at evaluating the preparedness of Indian organizations for receptivity and implementation in daily operations, recruiting, and financial resources. Experimentation in NFT commercialization is a goal of this project. An expert panel of five validates a well- structured questionnaire used in the study. In addition to demographic data and Likert scale questions, the survey contained demographic information and Likert scale questions. This research collects both primary and secondary data for its findings. After conducting a pilot research and meeting with consultants, a standard questionnaire is used prepared and used to collect the primary data. Secondary data is sourced from other fields of study, such as journals, websites, books, and magazines. The Cochran formula for an unknown population selects a random sample of 100 persons with a 10% margin of error and a 95% confidence level because there are no standard data on the number of investors. Out of 93 answers, 72 were selected for the study after the outliers were removed. Professionals in the workforce, employees of large corporations, investors, both professional and private, and members of the company’s upper management were all included in the study. Many influential company leaders and managers who implement new strategies, policies, and practises are among those who have agreed to participate in the study. For descriptive statistics - SPSS was used, and for SEM – AMOS was used. Many more people are aware with block chain and cryptocurrencies than of NFT technology, which is surprising. Blockchain-based technology platforms like cryptocurrencies and non-fungible tokens are premature due to their novelty and lack of effective implementations. An uncontrolled experimentation, which will probably take years to mature and trickle down into commercial applications, where it will have deep and far-reaching ramifications for society.